2021
DOI: 10.3390/ani11082355
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Plasma Metabolites of Grazing Beef Cattle Backgrounded on Buffel or Buffel-Desmanthus Mixed Pastures

Abstract: Dietary crude protein and dry matter digestibility are among the major factors limiting feed intake and weight gain of cattle grazing native and improved pastures in the subtropics of Northern Australia during the dry season. Incorporating a suitable legume into grasses improves pasture quality and cattle weight gain, but only a limited number of legume pastures can establish and persist in cracking clay soils. This study aimed to evaluate the effect of Desmanthus inclusion in buffel grass (Cenchrus ciliaris) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
(115 reference statements)
1
5
0
Order By: Relevance
“…In contrast, Loken et al ( 15 ) reported similar finishing DMI, ADG and feed to gain ratio in beef steers fed to attain low (1.4 kg/day) or high (1.6 kg/day) weight gain during the backgrounding period. In the current study, the ADG during backgrounding was similar for steers on either pasture type (0.74–0.75 kg/day) ( 29 ), hence the similar DMI, feed to gain ratio and final LW were expected.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, Loken et al ( 15 ) reported similar finishing DMI, ADG and feed to gain ratio in beef steers fed to attain low (1.4 kg/day) or high (1.6 kg/day) weight gain during the backgrounding period. In the current study, the ADG during backgrounding was similar for steers on either pasture type (0.74–0.75 kg/day) ( 29 ), hence the similar DMI, feed to gain ratio and final LW were expected.…”
Section: Discussionsupporting
confidence: 52%
“…Steers were backgrounded as described previously ( 29 ) in a commercial beef pastoral property located in central Queensland (24°41′ S, 147°10′ E), Australia. In summary, 400 15–18-month-old Bos indicus × Bos taurus tropical composite steers weighing 320 ± 21 kg were divided into two groups of 200 steers and randomly assigned to graze either in a paddock of buffel grass only or buffel grass pastures oversown with a blend of three desmanthus species, D. leptophyllus, D. virgatus and D. bicornutus , for 147 days.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, more studies are required to determine desmanthus’ effect on beef cattle growth performance and change in rumen and plasma metabolites. Our previous study [ 18 ], demonstrated that in an extensive grazing system typical of Central Queensland, Brigalow region, backgrounding 400 beef cattle steers during the dry season for 147 days on buffel grass alone or buffel-desmanthus mixed pastures with desmanthus accounting for 11.5% pasture biomass, did not produce any significant differences in liveweight, daily weight gain and plasma metabolites. The lack of difference was thought to be due to similar dietary crude protein levels for steers on both paddocks accessed through browsing on shrubs and forbs, necessitating the need for feeding steers isonitrogenous diets with varying levels of desmanthus inclusion in a controlled pen trial.…”
Section: Introductionmentioning
confidence: 99%
“…Backgrounding is a post-weaning feeding and growing program that produces cattle suitable to enter feedlots at approximately 280–400 kg ( Mwangi et al. 2021a ; Peel, 2003 ; Thomson & White, 2006 ).…”
Section: Backgroundingmentioning
confidence: 99%
“… Bowen and Chudleigh (2021a) suggested key strategies for improving and sustaining extensive livestock production systems that are drought resilient and more profitable across northern Australia's beef enterprises. These include drought-preparedness ( Rolfe et al., 2021 ), optimal steer sale age, breeder body condition and herd structure, effective phosphorus supplementation ( Bowen et al., 2020 ) and improvement in steer nutrition through tropically adapted perennial legume grass pastures ( Mwangi et al., 2021a ; Mwangi et al., 2021b ). Fordyce et al., (2021) defined the primary business measure of liveweight production for beef cows in northern Australia and reported that liveweight production in breeding beef cows was primarily governed by available nutrition and mating outcome.…”
Section: Introductionmentioning
confidence: 99%